Formation and Development of Transnational Hotel Chains in Modern Environment - MOROZOVA, Lyubov Semenovna; MOROZOV, Vladimir Yuryevich; HAVANOVA, Natalya Vladimirovna; DUBORKINA, Irina Albertovna; ARIFULIN, Marat Venerovich (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017DO - 10.14505//jemt.v8.2(18).04, 2017)
The study investigates the issues of the genesis of basic ideas associated with the functions of the network systems in hotel industry, specifies such ideas as “hotel net” and “hotel chain” and also provides the analysis of transnational hotel corporations as the most efficient organizational form in hotel business. The post-Soviet development of tourism industry and of the hospitality sector as of one of its most important constituent elements in Russia has unveiled the ever increasing misbalance between the demand for the high-quality products (services) on behalf of the consumers and the capabilities of the most hotel companies to ensure the qualitative and quantitative parameters of the services to supply the market. Development of the travel and hospitality industry under the modern conditions in Russia raises a number of new problems. One of them is represented by the lack of any sufficiently structured methodology and methods for establishing the transnational hotel chains (THC). The world practices of the hotel business development demonstrate convincingly that the most adequate and economically feasible form of operations of the hotel companies is represented by the hotel chains of national and transnational scale which, however, have not been developed extensively enough in this country.